CHEMIA NAPOCENSIS 1919-2019 - SILAGHI-DUMITRESCU, Luminita (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The centenary of the University of Cluj gives us the opportunity for a retrospective reflecting on the beginnings, development and contributions of the Cluj School of Chemistry to the Romanian scientific research and its presence in the international chemical science. We must say from the beginning that the outcomes are not negligible, although for a long time the conditions were not comparable to those in more advanced countries. Several generations have succeeded in the Cluj School of Chemistry, each bringing beyond the specialized training of the students something new in scientific preoccupations, in accordance with the development of chemistry and the emergence of new fields. Since its foundation, immediately after the establishment of the Romanian University in Cluj, the chemistry - enrolled in the Faculty of Sciences, has also became noticeable in scientific research, thanks to the founding teachers who were not satisfied with a remarkable didactic activity, but also lighted the scientific spirit in the activity of the new institution.